A Multi-Criteria Decision Making Approach for Enhancing University Accreditation Process - Benmoussa, N.; Elyamami, A.; Mansouri, K.; Qbadou, M.; Illoussamen, E. (Engineering, Technology & Applied Science Research, 2019)
This paper is an attempt to provide an accreditation training process model by the criteria established by the National Agency for Evaluation and Quality Assurance of Higher Education and Training. The aim is to minimize rejection returns or revisions of the training record. The main feature of our contribution is the use of multi-criteria decision making (MCDM) approaches for calculating the suitability of proposed courses. Therefore, our contribution will is concretized by the analysis of various decision support multi-criteria methods, the modeling of the general accreditation process of university courses, the development of a risk management matrix concerning the launch of new courses and the application of TOPSIS (technique for order of preference by similarity to ideal solution) on a sample of courses according to internal and external criteria, collected during interviews in Moroccan universities. Result analysis shows that the proposed model allows a better prioritization of training and thus avoids the abrupt closure of courses because of lack of material or human resources.